Eugenol and lidocaine inhibit voltage-gated Na+ channels from dorsal root ganglion neurons with different mechanisms - Moreira-Junior, Luiz; Leal-Cardoso, Jose Henrique; Cassola, Antonio Carlos; Carvalho-de-Souza, Joao Luis (Frontiers in Pharmacology, 2024)
Eugenol (EUG) is a bioactive monoterpenoid present in human culture as an analgesic, preservative, and flavoring. Our new data show EUG as a voltage-gated Na+ channels (VGSCs) inhibitor, comparable but not identical to lidocaine (LID). EUG inhibits both total and only TTX-R voltage-activated Na+ currents (INa) recorded from VGSCs naturally expressed on dorsal root ganglia sensory neurons from rats. Inhibition is quick, fully reversible, and dose-dependent. Our biophysical and pharmacological analysis showed EUG and LID inhibit VGSCs with different mechanisms. EUG inhibits VGSCs with a dose-response relationship characterized by a Hill coefficient of 2, while this parameter for the inhibition by LID is 1. Also in a different way compared to LID, EUG modified the voltage dependence of both the VGSCs activation and inactivation processes, as well as the recovery from fast inactivated states and the entry to slow inactivated states. In addition, we would like to suggest EUG, but not LID, interacts with VGSCs pre-open closed states, according to our data.